The quality of life of the Bahau riverside community: the case of the rural community living along Muar and Serting rivers - Ramli, Siti Aisyah; Md. Yassin, Sulaiman; Idris, Khairuddin; Hamzah, Azimi; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2013)
Quality of Life (QOL) is encompassed in people's satisfaction with regards to various aspects of their existence. Many QOL studies have been pursued worldwide and some of these are focused upon the rural community. This study aims to investigate the QOL of the riverside community living in Bahau which is an area in Negeri Sembilan, Malaysia. This is a quantitative study in which a total of 300 villagers that live near to Muar and Serting rivers were chosen as the respondents. The survey method was employed to obtain the data while SPSS was performed to run suitable and relevant analyses. Generally, the analyses confirm that rural communities living near to Muar and Serting rivers in Bahau have a moderate QOL. Specifically, the respondents were found to have a better QOL in terms of their home conditions but not with respect to infrastructure facilities. A number of discussions and recommendations are put forward in this study and it is hoped that these can be used by concerned parties for the development of Bahau.